THE LEGAL NATURE OF THE PERIOD FOR APPLYING TO THE COURT FOR ADMINISTRATIVE PROCEEDINGS - YUDIN Andrey Vladimirovich (Правовое государство: теория и практика, 2022)
In cases of administrative proceedings in courts of general jurisdiction and in arbitration courts, a general period of three months is established for an application to the court to challenge unlawful acts of authorities. This term is almost unconditionally positioned in judicial practice and in most scientific studies as a procedural term with all the accompanying consequences concerning the regime of restoration of the term, consequences of its omission, etc. Meanwhile, such an approach raises doubts due to the different legal nature of the period for applying to the court; the analysis of this nature is the purpose of the study. Purpose: based on a critical assessment of the approaches of judicial practice and doctrinal views that a priori classify such a period as procedural, to establish the legal nature of the period for applying to the court for administrative proceedings, mainly in the direction of attributing such a period to procedural or substantive legal terms. Methods: empirical methods of comparison, description, interpretation; theoretical methods of formal and dialectical logic; specific scientific methods: legal-dogmatic and interpretation of legal norms. Results: the study reveals that the three-month period established for applying to the court in order to challenge acts of authorities is by its nature a substantive legal period, an analogue of the limitation period in administrative legal relations; positioning such a period as a procedural one with all the attendant consequences is erroneous. The term considered in the article is named by the procedural law as the term for applying to the court or as the term for filing an application, which seems to be erroneous in the light of understanding this term as the term for protecting the right at the request of a person whose right is violated.